1993
DOI: 10.1063/1.109014
|View full text |Cite
|
Sign up to set email alerts
|

Large critical currents and improved epitaxy of laser ablated Ag-doped YBa2Cu3O7−δ thin films

Abstract: Microstructure and critical current densities of laser ablated YBa2Cu3O7−δ thin films doped with 2–20 wt. % Ag have been studied. A critical current density as high as 1.4×107 A cm−2 at 77 K has been realized on 〈100〉 SrTiO3 substrates with YBaCuO films doped with 5 wt. % Ag which has been found to be the optimum. Evidence indicates that the improved microstructure and epitaxy which is a consequence of grain enlargement and alignment caused by Ag is responsible for the high values of critical currents observed. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
31
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 14 publications
2
31
0
Order By: Relevance
“…The incorporation of secondary phase nano-particles into films is a promising concept for enhancing J c enhancement, since this enables type, density and distribution of such nano-materials to be varied and, consequently, the magnetic flux pinning properties of the films to be optimised. Different types of nano-particles including Ag [2], BaIrO 3 [3], BaSnO 3 [4], BaZrO 3 [5,6,7,8,9], Y 2 BaCuO 5 [10,11], [12,13,14] and Y 2 O 3 -stabilized ZrO 2 [15] have been shown to increase the J c of Y-123 based composite layers compared to that of phase pure Y-123 films.…”
mentioning
confidence: 99%
“…The incorporation of secondary phase nano-particles into films is a promising concept for enhancing J c enhancement, since this enables type, density and distribution of such nano-materials to be varied and, consequently, the magnetic flux pinning properties of the films to be optimised. Different types of nano-particles including Ag [2], BaIrO 3 [3], BaSnO 3 [4], BaZrO 3 [5,6,7,8,9], Y 2 BaCuO 5 [10,11], [12,13,14] and Y 2 O 3 -stabilized ZrO 2 [15] have been shown to increase the J c of Y-123 based composite layers compared to that of phase pure Y-123 films.…”
mentioning
confidence: 99%
“…(where ξ(T) is the Ginzburg-Landau coherence length at temperature T) above which the superconductivity gets destroyed due to the vanishing of the energy gap. In an actual measurement of critical current, this limit is rarely achieved in high temperature superconducting film due the large size of the micro-bridge compared to the coherence length and due to the presence of weak links arising from the grain boundaries in the sample 12 . This quantity varies with temperature as (1-(T/T c )) 3/2 (Strictly speaking this mean field relation holds only at temperature close to T c .)…”
mentioning
confidence: 99%
“…In the case of cuprate superconductors, the films grown by pulsed laser deposition (PLD) from Ag-superconductor composite targets show an improvement in microstructure and an enhancement in critical current density (J C ). [2][3][4][6][7][8][9] Some of the reports show an optimum value of Ag in the target is essential to achieve the best results. 2,9 Amid the improvement in microstructure and other physical properties in these films, the final film always contained some amount of Ag.…”
mentioning
confidence: 99%
“…[2][3][4][6][7][8][9] Some of the reports show an optimum value of Ag in the target is essential to achieve the best results. 2,9 Amid the improvement in microstructure and other physical properties in these films, the final film always contained some amount of Ag. 2,7,9,[12][13][14] Also, it has been found that Ag stays in the metallic form.…”
mentioning
confidence: 99%
See 1 more Smart Citation